2017
DOI: 10.1021/acs.inorgchem.7b02642
|View full text |Cite
|
Sign up to set email alerts
|

The Mineral Stützite: a Zintl-Phase or Polar Intermetallic? A Case Study Using Experimental and Quantum-Chemical Techniques

Abstract: Differing reports regarding the structural features of the mineral stützite, AgTe (-0.25 ≤ x ≤ 1.44), and the quest for tellurides with low-dimensional fragments stimulated our impetus to review this system by employing experimental as well as quantum-chemical methods. Determination of the crystal structures for three samples with compositions AgTe (I), AgTe (II), and AgTe (III) revealed considerable positional disorders for the Ag and Te sites and previously unknown structure models for I and II, which differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Under consideration of previous research [37,38] on the electronic structures of alkaline-metal-containing polar intermetallics, this outcome suggests that the Rb-Te interactions should be considered as ionic interactions, while the Pr-Te and Ag-Te interactions should be regarded as rather strong, polar, mixed-metal bonds. This outcome also indicates that a full valence-electron transfer as proposed by an application of the Zintl-Klemm concept should be regarded with suspicion-a consequence which has also been identified by recent explorations of the electronic structures of rare-earth transition-metal tellurides [22] as well as silver tellurides [21]. The homoatomic Ag-Ag interactions change from bonding to considerable antibonding states at −4.41 eV, which may be regarded as attributes of the d 10 -d 10 closed-shell [39,40] interactions; however, the Ag-Ag -ICOHP values are indicative of a net bonding character for these interactions.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…Under consideration of previous research [37,38] on the electronic structures of alkaline-metal-containing polar intermetallics, this outcome suggests that the Rb-Te interactions should be considered as ionic interactions, while the Pr-Te and Ag-Te interactions should be regarded as rather strong, polar, mixed-metal bonds. This outcome also indicates that a full valence-electron transfer as proposed by an application of the Zintl-Klemm concept should be regarded with suspicion-a consequence which has also been identified by recent explorations of the electronic structures of rare-earth transition-metal tellurides [22] as well as silver tellurides [21]. The homoatomic Ag-Ag interactions change from bonding to considerable antibonding states at −4.41 eV, which may be regarded as attributes of the d 10 -d 10 closed-shell [39,40] interactions; however, the Ag-Ag -ICOHP values are indicative of a net bonding character for these interactions.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 79%
“…To provide an insight into the bonding situation in RbPr2Ag3Te5, we followed up with an examination of the crystal orbital Hamilton population curves (COHP; Figure 2) and their respective integrated values (Table 3). In this context, the cumulative -ICOHP/cell values, i.e., the sums of the negative ICOHP/bond values of all nearest neighboring contacts within one unit cell, were projected as percentages of the net bonding capabilities for each sort of interaction to identify roles of the diverse interactions in overall bonding-a procedure that has been largely employed elsewhere [21,22,[33][34][35][36]. (Figure 2) reveals that the occupied states close to the Fermi level, E F , originate to a large extent from the Ag-d and Te-p atomic orbitals beside minor contributions from the Pr-d states.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both orbital-based Mulliken and Löwdin population analyses as implemented in LOBSTER automatically and accurately derive atomic charges in solid-state materials, and we will demonstrate their performance as regards ionic compounds, polar intermetallics, including commonly known archetypal Zintl phases, as well as another polar intermetallic compound, i.e., stützite. 54 The latter mineral was chosen for the prototypical application of the tool, as more recent research 54 revealed that applying the Zintl-Klemm concept to it should be taken with a pinch of salt. For comparison, density-based Bader charges were also calculated for the present compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the light of such relevance for research and technical applications, one could also expect that the nature of bonding in tellurides is typically examined employing first-principles-based approaches; yet, the electronic structures, particularly the nature of bonding, in many tellurides are frequently (and simplistically) interpreted by applying the Zintl-Klemm concept rather than first-principles-based bonding analyses [15]. More recent research [16][17][18] on the electronic structures of certain tellurides, however, demonstrated that such Zintl-Klemm pictures should be taken with a pinch of salt. In fact, examining the electronic structures of (active-metal) transition-metal tellurides (active-metal = group I and III elements) revealed that the bonding nature in these tellurides is dominated by strong transition-metal−tellurium interactions beside minor transition-metal−transition-metal or tellurium−tellurium interactions.…”
Section: Introductionmentioning
confidence: 99%